Mapping Climate Changes in Iraq By Using Geographical Information System (GIS) - Sahib Jawad, Zainab; Asaad Tayeb, Fatima; Kareem Jebur, Asaad Tayeb (International Journal of Engineering and Technology, 2018)
The Trapped sun’s thermal radiation in the earth’s atmosphere is known as the greenhouse effect.  This process is considered very important since it keeps the earth warm and hence possible to live in. Greenhouse gases such as carbon dioxide (CO2) and methane (CH4) are considered very important contributors to the greenhouse effect. During the last two decades, the level of greenhouse gases has increased, which plays a major role in global warming and climate change. The Middle East is considered among the most affected areas by climate change. In the current study, Geographical Information System (GIS) has been used to create some temperature maps that could show the air temperature distribution and difference between two different periods of time (past and recent) in different stations that cover the Iraqi governorates. A spatial interpolation method has been used. This method considers known values of temperature at a given location (stations in the current study) to estimate a continuous surface map during a specific period of time. The results of this study showed no significant increase in the average air temperature values, however the area of high air temperature values is growing during the cold and hot months of the year.